1982
DOI: 10.3109/00016488209130874
|View full text |Cite
|
Sign up to set email alerts
|

The Ototoxic Interaction of Viomycin, Capreomycin and Polymyxin B With Ethacrynic Acid

Abstract: The ototoxic interaction between the aminoglycoside antibiotics (streptomycin, kanamycin, etc.) and the loop-inhibiting diuretics (ethacrynic acid, furosemide and bumetanide) has been well documented. This interaction causes extensive destruction of the hair cells of the cochlea. Brummett et al. (1974) demonstrated that this interaction did not occur with the non-loop-inhibiting diuretics and kanamycin. The present study was undertaken to determine if antibiotics other than the aminoglycosides could produce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Lutz et al 28 found no difference in hearing loss or cochlear hair cell count between guinea pigs receiving a range of vancomycin doses < 300 mg/kg/d for 11 to 17 days and control animals, similar to the findings of others using guinea pig and gerbil models. [28][29][30][31][32] Brummett et al 14,18 have previously summarized the evidence supporting the rarity of vancomycin-associated ototoxicity. Aronoff 33 was unable to detect alteration of renal function in rats at vancomycin doses < 400 mg/kg/d, similar to the observation of others in guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Lutz et al 28 found no difference in hearing loss or cochlear hair cell count between guinea pigs receiving a range of vancomycin doses < 300 mg/kg/d for 11 to 17 days and control animals, similar to the findings of others using guinea pig and gerbil models. [28][29][30][31][32] Brummett et al 14,18 have previously summarized the evidence supporting the rarity of vancomycin-associated ototoxicity. Aronoff 33 was unable to detect alteration of renal function in rats at vancomycin doses < 400 mg/kg/d, similar to the observation of others in guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple reports of this adverse reaction can be found in the literature, there are no reports of ototoxicity in experimental animals. Davis et al 12 failed to demonstrate ototoxicity of vancomycin in guinea pigs even when the animals were also treated with ethacrynic acid, a drug that augments the ototoxic effects of other ototoxic drugs. Brummett et al 13 guinea pigs and found that vancomycin alone was not ototoxic, but the ototoxic effect was greatly enhanced when vancomycin was administered with gentamicin.…”
Section: Discussionmentioning
confidence: 99%